Overexpression of microRNA-21 strengthens stem cell-like characteristics in a hepatocellular carcinoma cell line. Issue 1 (December 2016) - Jiang, Jinghang; Yang, Peipei; Guo, Zhe; Yang, Rirong; Yang, Haojie; Yang, Fuquan; Li, Lequn; Xiang, Bangde
Abstract Background Liver cancer stem cells (LCSCs) have been shown to express higher levels of microRNA-21 (miR-21). Here, we examine the possible contributions of miR-21 to the phenotype of LCSCs in culture and in xenograft tumors in nude mice. Methods The hepatocellular carcinoma cell line MHCC-97H was stably transformed with a retroviral vector to establish cells overexpressing miR-21, while a cell line transformed with empty vector served as a negative control. RT-PCR and Western blotting were used to evaluate the effects of miR-21 overexpression on the expression of various LCSC markers, a Transwell assay was used to assess the effects on cell migration and invasion, and a spheroid formation assay was used to examine the effects on clonogenesis. The effects of miR-21 overexpression were also examined in tumors in nude mice. Results An MHCC-97H cell line was constructed that stably overexpresses miR-21 at 7.78 ± 1.51-fold higher levels than the negative control cell line. Expression of the LCSC markers CD13, Ep-CAM, CD90, and OCT4 was significantly higher in the miR-21-overexpressing cell line than in the negative control at both mRNA and protein levels. The overexpressing cell line formed larger, tighter, and more numerous spheroids. Overexpression of miR-21 was associated with greater cell migration and invasion. Tumors of overexpressing cells in nude mice had a significantly larger mean volume after 34 days of growth (773.62 ± 163.46 mm3 ) than tumors of negative control cells (502.79 ± 33.94 mm3, p = 0.048), as well as greater mean weight (0.422 ± 0.019 vs. 0.346 ± 0.006 g, p = 0.003). Conclusions Overexpression of miR-21 strengthens the phenotype of LCSCs, facilitating invasion, migration, and tumorigenesis in hepatocellular carcinoma.